Human-Induced on Timber Concrete Composite (TCC) and Reinforced Concrete (RC) Flooring System - Anuar, Siti Fatima Najwa; Abd Ghafar, Nor Hayati (Recent Trends in Civil Engineering and Built Environment, 2025)
The study conducted at a building located in Sri Alam Pasir Gudang, Johor involved walking tests on timber concrete composite (TCC) and reinforced concrete (RC) floors to stimulate human-induced vibrations. The result reveals that the natural frequency for both TCC and RC floors ranges from 10.35Hz to 51.27Hz and 13.67Hz to 51.27. These natural frequencies exceed the 8Hz comfort range for human comfort. The wave propagation graph shows the middle floor of both floors is the critical area. The analysis concludes that TCC floors, due to their low-frequency nature, exhibit more significant weakness to deformation vibrations, resulting in weakened serviceability compared to RC floors. Comprehending these vibration behaviour is important in the field of structural design within the construction industry, as discomfort caused by floor vibrations influences how occupants perceive safety and comfort.